Locality-based and place-based development in theory and practice – an example of the Hungarian countryside - József Lennert; Bálint Csatári; Jenő Zsolt Farkas; Dávid Mezőszentgyörgyi (DETUROPE)
Local development has been always considered an important instrument in the renewal of the rural economy, society and settlements, but recent changes of rural areas led to the conceptual expansion of the term. Besides locality-based development, the significance of the novel concept of place-based development has also been recognised. Place-based development not only takes the local characteristics into account, but tries to harmonise the development processes of the different sectors and territorial levels. The core of place-based approach is the well-coordinated, multilateral and continuous communication between the actors and institutes from different territorial levels and different sectors. Our paper provides an overview of the concepts of locality-based and place based development, and investigates their applicability to the development of the Hungarian rural areas. The presented results of a survey which involved the experts in the Hungarian National Rural Network provide additional information about the Hungarian rural development and the necessity of place-based approach.